EKSISTENSI PRANATA HUKUM DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA - Enny Agustina (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2020)
The interaction between the nations has influenced the pattern of life and new demands which have never been obtained. However, among the impacts that arise, it turns out that there are more negative impacts on the order of life of the Indonesian nation. The pattern of social life has shifted to individualism, deliberation has shifted to voting and controversy, and consumptive life has become the preferred choice. Changes in the pattern and order of life have broad consequences, including, corruption seems to be a common thing, violent conflict becomes a model for problem solving, and discipline and obedience to regulations are weak. The problem in this study is the existence of legal institutions in the life of the nation and state and legal culture in the institutions of national and state life. The research method in this study is a normative juridical approach in which the literature used is to use legislation, as well as books. The conclusion in this study is that the existence of local wisdom-based institutions is very important because it has been integrated into the order of community life. The substance is implicit in the Pancasila Grundnorm and the 1945 Basic Law, but in the legislation it has not yet got its proper place, causing behavior that deviates from the system of national and state life. The concept of local wisdom in the life of the nation and state as described above, if understood, lived and implemented, will realize its main goal, namely a harmonious and cultured life order between the leaders and the people, as well as law enforcement and justice so that a prosperous life order can be achieved, just and prosperous for all the people of the Republic of Indonesia